Reframing birth: a consequence of cesarean section - Fenwick, Jennifer; Gamble, J.; Hauck, Yvonne (Blackwell Publishing Ltd, 2006)
Aim:This paper is a report of a study to describe the childbirth expectations, influences and knowledge of a group of Western Australian women who experienced a cesarean section (CS) and would prefer a CS in a subsequent pregnancy.Background:Evidence suggests that a previous CS is not an indication for an elective CS in a subsequent pregnancy, but western world data indicate high probability of repeat CS.Methods:Community advertisements invited women who had experienced a CS to participate in a telephone interview. The thematic analysis presented in this paper is derived from data collected during 2003/2004 from 49 participants who had initially expected to birth vaginal but had a CS and who had planned a CS in a subsequent pregnancy or stated that they would choose this option in a future pregnancy.Findings:Before the first CS most women expected and wanted to give birth normally. After having a CS, however, many reframed vaginal birth as uncertain, unsafe and unachievable. For this group of women, the medical discourse that promoted CS as the safest option was a major influence on their decisions. As a result, they reconstructed CS as an acceptable alternative that was safer for them and their babies, allowed them to be better prepared, and was convenient.Conclusion:In the present climate, enabling women to keep birth 'fear' in perspective may be an important strategy if we are to improve the uptake of vaginal birth after CS and the quality of care offered to women during the normal, but major, life event of childbirth.